Public Investment Management in Latin America and the Caribbean : Institutions under Evolution - Frank, Jonas (World Bank, Washington, DC, 2014)
Over recent decades many countries of the Latin America region have set up specialized processes and mechanisms for public investment management. Initially created as isolated systems, they are now being further integrated with enhanced budgeting processes and financial management systems. In this process, Ministries of Finance and planning entities have emerged as the two key agencies taking on critical functions in the investment cycle. The on-going consolidation of institutional arrangements is being challenged through the increasing involvement of subnational governments, not least since they also are increasingly promoting PPP arrangements that require considerable regulatory capacities. More recently, countries are promoting results-oriented management and multi-year planning which can provide new impetus to strengthen public investment management. This is required as infrastructure gaps remain significant across urban and rural areas, and further efforts are required to enhance expenditure efficiency at both national and subnational levels of government. In the future, increased attention and asymmetric treatment of subnational governments is required to address the existing and possibly widening infrastructure gaps in light of uneven capacities.